2021
DOI: 10.1371/journal.pone.0257244
|View full text |Cite
|
Sign up to set email alerts
|

Tidal marsh restoration enhances sediment accretion and carbon accumulation in the Stillaguamish River estuary, Washington

Abstract: Tidal marshes have been recognized globally for their ability to sequester “blue carbon” but there is still a need for studies investigating the marsh response to restoration, particularly in the Pacific Northwest United States. Here we report carbon stocks and accumulation rates for restored and natural tidal marshes in the Stillaguamish River estuary in Puget Sound, Washington, where a 60-hectare marsh was reintroduced to the tidal regime from its previous use as diked and drained farmland. We found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Conservation of existing carbon stocks in natural marshes is therefore often prioritized as a climate change mitigation strategy over restoration (Macreadie et al, 2017). Recent evidence from the USA, however, found carbon stocks in the top 30 cm of a MR site were only marginally lower than adjacent natural sites in the 4 years following restoration (4.43 and 5.95 kg C m -2 respectively; Poppe and Rybczyk, 2021). The various timescales reported for the development of carbon stocks in restored saltmarshes are highly site-specific -an important consideration for MR as a technique to enhance climate change mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Conservation of existing carbon stocks in natural marshes is therefore often prioritized as a climate change mitigation strategy over restoration (Macreadie et al, 2017). Recent evidence from the USA, however, found carbon stocks in the top 30 cm of a MR site were only marginally lower than adjacent natural sites in the 4 years following restoration (4.43 and 5.95 kg C m -2 respectively; Poppe and Rybczyk, 2021). The various timescales reported for the development of carbon stocks in restored saltmarshes are highly site-specific -an important consideration for MR as a technique to enhance climate change mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…These factors have been shown to increase the speed of recovery of wetland functions at restored sites (e.g. Moreno‐Mateos et al 2012; Yu et al 2017; Poppe & Rybczyk 2021) and may have promoted the recovery of wetland functions at the passively restored site. Deposits from the Big Creek channel likely elevate burial of allochthonous organic carbon and minerogenic sediments and help preserve autochthonous organic matter in deeper sediment layers (Kemp et al 2019; Spivak et al 2019), in part explaining the high rates of carbon accumulation at the reference and passively restored marshes.…”
Section: Discussionmentioning
confidence: 99%
“…We note that, within this system, the partitioning between high and low marsh zones appears very closely linked with associated vegetation. Therefore, vegetation composition was recorded as an indicator of "low" vs. "high" marsh zones (Porter, 1982;Weinmann et al, 1984) around each coring spot. Coring spots were considered low marsh if the species Triglochin maritima, Salicornia spp., Fucus ssp., or Distichlis spicata were present and high marsh if it included Plantago maritima, Deschampsia caespitosa, Grindelia integrifolia, Potentilla anserina, Lysimachia maritima, or Eleocharis ssp.…”
Section: Field Samplingmentioning
confidence: 99%
“…Several recent studies have shown substantially higher CARs in restored vs. natural marshes after approximately 10 years (e.g. Poppe and Rybczyk, 2021;Drexler et al, 2019). The causes of these inflated CARs can be very site-specific, depending on the types of colonizing vegetation (Kelleway et al, 2017) and the relative contributions of allochthonous mineral materials (Drexler et al, 2019).…”
Section: Comparison Of Whole-core and 30-year Carsmentioning
confidence: 99%